First, let's look at the expression using the order of operations:
6 / 3 + 4 ÷ 2 + 4 / 4
According to the order of operations, we need to perform multiplication/division before addition/subtraction.
Let's start with the division:
6 ÷ 3 = 2
4 ÷ 2 = 2
Now we can rewrite the expression:
2 + 2 + 4 / 4
Next, let's perform the addition:
2 + 2 = 4
Now our expression becomes:
4 + 4 / 4
Finally, let's perform the last division:
4 ÷ 4 = 1
Our final simplified expression is:
4 + 1 = 5
Use the order of operations to simplify: 6/3 +4÷2+4/4.
1 answer